Respostas

2014-07-12T15:02:06-03:00
1 -

10 (4p + 5q) 

40p + 50q 
90pq 

7x (x - 5) 
7x² - 35
7x² = 35
x² = 35 / 7
x² = 5
x = + ou - √5

(x² - y) x
x³ - xy
x (x² - y) = 0
x = 0

x² - y = 0
x² = y 

-3t ( - 2t - 4 )
- 6t² - 12t . (- 1)
6t² + 12t 
t (6t - 12) = 0
t = 0

6t -12 =0
6t = 12
t = 12 / 6
t = 2

2 - 

7x² +2 ( x² - 1 )

7x² + 2x² - 2
9x² - 2 = 0
9x² = 2
x² = 2 / 9
x = + ou - √2 / 9

10 - 4 ( x - 3 ) + 5
10 - 4x - 12 + 5  = 0
- 4x - 12 + 5 + 10 = 0
- 4x + 3 = 0  ( - 1)
4x - 3 = 0
4x = 3
x = 3 / 4
4 5 4